1992
DOI: 10.1089/lps.1992.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy in Situs Inversus Totalis

Abstract: A 51-year-old woman with known dextrocardia presented with left-sided abdominal pain and symptoms consistent with biliary colic and cholelithiasis. Abdominal ultrasound confirmed the diagnosis of gallstones, as well as situs inversus with the liver and gallbladder on the left side and the spleen on the right. Laparoscopic cholecystectomy was performed without incident. The procedure was uncomplicated except for being the mirror image of that done with the gallbladder in the normal location. Cholelithiasis occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 10 publications
0
50
0
2
Order By: Relevance
“…[1][2][3][4] The cause of the transposition is unknown, but it is claimed to be due to a genetic predisposition, with an autosomal recessive transmission. Associated anomalies are known to be quite frequent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The cause of the transposition is unknown, but it is claimed to be due to a genetic predisposition, with an autosomal recessive transmission. Associated anomalies are known to be quite frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Since first performed by Mouret in France in 1987, laparoscopic cholecystectomy has rapidly evolved as the standard therapeutic modality for gallstone disease, after it was refined and popularized in the United States by Reddick and Olsen. 1 Drover et al reported the first case to have laparoscopic cholecystectomy with this type of anomaly. 5 Although the intrahepatic and extrahepatic biliary anatomy are mirror images of normal, there is a higher likelihood of associated anomalies, which might add an additional challenge to performing a laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8][9][10][11][12] In two different cases reported, 5,6 the pain was recurrent and located in the left upper quadrant of the abdomen. Others have reported that the pain of biliary colic in patients with situs inversus may occur in the epigastrium or the right or left upper quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly due to the abnormal spatial relationship of the gallbladder, cystic duct and cystic artery. However, since it is the mirror image of what is done with the gallbladder in the normal location, 6 once the surgeon is able to re-orient himself, the technical difficulty is easily overcome.…”
Section: Discussionmentioning
confidence: 99%
“…• Situs inversus totalis does not appear to be a contraindication [1,4] to laparoscopic cholecystectomy even in case of empyema [3].…”
Section: Recommendations and Future Scopementioning
confidence: 99%